The Application of Project Based Learning to Improve Students’ Ability in Analyzing Narrative Texts of English for SMA - Rosyad, Laili (Center of Language and Cultural Studies [CLCS], 2020)
The purpose of this study was to improve English learning achievement through the application of the Problem Based Learning for grade XII of class IPA.1 students at SMA Negeri 1 Mlonggo. This research is a collaborative classroom action research, assigning 30 students of class IPA-1 of SMA Negeri 1 Mlonggo as the research participants. Data were collected through observation and test. This research has two cycles. Each implements four stages, namely planning, implementation, observation and evaluation, analysis and reflection. Each cycle is carried out in three meetings with 2x45 minutes each. Results show that the increase of respective cycles is as follows: (1) of 36 students, 20 (57%) achieved the mastery learning in the pre-cycle, (2) in the first cycle, 26 (74%) students completed the mastery learning, and (3) in the second cycle, 34 (97%) finished the minimum learning mastery. In average, the achievement in pre-cycle 72.86 increase into 79.00 (8%) in cycle I, and into 84.29 (16%) in cycle II.